Evidence-based occupational health and safety interventions: a comprehensive overview of reviews - Teufer, Birgit; Ebenberger, Agnes; Affengruber, Lisa; Kien, Christina; Klerings, Irma; Szelag, Monika; Grillich, Ludwig; Griebler, Ursula (BMJ open, 2019)
ObjectivesOccupational injuries and diseases are a huge public health problem and cause extensive suffering and loss of productivity. Nevertheless, many occupational health and safety (OHS) guidelines are still not based on the best available evidence. In the last decade, numerous systematic reviews on behavioural, relational and mixed interventions to reduce occupational injuries and diseases have been carried out, but a comprehensive synopsis is yet missing. The aim of this overview of reviews is to provide a comprehensive basis to inform evidence-based decision-making about interventions in the field of OHS.MethodsWe conducted an overview of reviews. We searched MEDLINE (Ovid), the Cochrane Library (Wiley), epistemonikos.org and Scopus (Elsevier) for relevant systematic reviews published between January 2008 and June 2018. Two authors independently screened abstracts and full-text publications and determined the risk of bias of the included systematic reviews with the ROBIS (Risk of Bias in Systematic Reviews) tool.ResultsWe screened 2287 abstracts and 200 full-texts for eligibility. Finally, we included 25 systematic reviews with a low risk of bias for data synthesis and analysis. We identified systematic reviews on the prevention of occupational injuries, musculoskeletal, skin and lung diseases, occupational hearing impairment and interventions without specific target diseases. Several interventions led to consistently positive results on individual diseases; other interventions did not show any effects, or the studies are contradictory. We provide detailed results on all included interventions.DiscussionTo our knowledge, this is the first comprehensive overview of behavioural, relational and mixed interventions and their effectiveness in preventing occupational injuries and diseases. It provides policymakers with an important basis for making evidence-based decisions on interventions in this field.PROSPERO registration numberCRD42018100341